Pertanggungjawaban Pidana Terhadap Pencurian Barang Penumpang Pesawat Studi Dibandara Udara Kualanamu Internasional Airport - Anjani Sipahutar (Universitas Islam Sumatera Utara, 2020)
This study aims to determine that there are still many events that are still require the liability from the commercial air transportation company, both from the carrier company and those who are related to the carrier, such as flight delays (flight delay) either caused by weather factors or internal factors from the carrier company, the occurrence of negligence from the transport officer which causes the loss of goods owned by passengers, or because of there is an event for which the reason is unknown so that the aircraft experiences interference during the flight, from the results of this research it can be seen that the carrier operating the aircraft is obliged to be responsible for losses against:a. passengers who died, disability or injury;b. lost or damaged of the cabin baggage;c. lost, destroyed, or damaged of the checked baggage;d. lost, destroyed, or damaged of the cargo;e. delay in air transportation; andf. losses suffered by third partiesas well as who are the parties involved, the requirements that must be fulfilled and how the rights and the obligations of the parties are fulfilled, as well as other provisions in its implementation if a passenger's goods are lost or damaged and provide a description of its protection.Keywords : Liability, Theft of Goods, Aircraft Passengers, Kualanamu International Airport.